Spatiotemporal Heterogeneity of Water Flowpaths Controls Dissolved Organic Carbon Sourcing in a Snow-Dominated, Headwater Catchment - Radke, Anna G.; Godsey, Sarah E.; Lohse, Kathleen A.; McCorkle, Emma P.; Perdrial, Julia; Seyfried, Mark S.; Holbrook, W. Steven (Frontiers in Ecology and Evolution, 2019)
The non-uniform distribution of water in snowdrift-driven systems can lead to spatial heterogeneity in vegetative communities and soil development, as snowdrifts may locally increase weathering. The focus of this study is to understand the coupled hydrological and biogeochemical dynamics in a heterogeneous, snowdrift-dominated headwater catchment (Reynolds Mountain East, Reynolds Creek Critical Zone Observatory, Idaho, USA). We determine the sources and fluxes of stream water and dissolved organic carbon (DOC) at this site, deducing likely flowpaths from hydrometric and hydrochemical signals of soil water, saprolite water, and groundwater measured through the snowmelt period and summer recession. We then interpret flowpaths using end-member mixing analysis in light of inferred subsurface structure derived from electrical resistivity and seismic velocity transects. Streamwater is sourced primarily from groundwater (averaging 25% of annual streamflow), snowmelt (50%), and water travelling along the saprolite/bedrock boundary (25%). The latter is comprised of the prior year’s soil water, which accumulates DOC in the soil matrix through the summer before flushing to the saprolite during snowmelt. DOC indices suggest that it is sourced from terrestrial carbon, and derives originally from soil organic carbon (SOC) before flushing to the saprolite/bedrock boundary. Multiple subsurface regions in the catchment appear to contribute differentially to streamflow as the season progresses; sources shift from the saprolite/bedrock interface to deeper bedrock aquifers from the snowmelt period into summer. Unlike most studied catchments, lateral flow of soil water during the study year is not a primary source of streamflow. Instead, saprolite and groundwater act as integrators of soil water that flows vertically in this system. Our results do not support the flushing hypothesis as observed in similar systems and instead indicate that temporal variation in connectivity may cause the unexpected dilution behavior displayed by DOC in this catchment.